Abnormal neurotransmission of GABA and serotonin in Caenorhabditis elegans induced by Fumonisin B1. (1st July 2022) - Zhang, Xiaojuan; Ye, Yongli; Sun, Jiadi; Wang, Jia-Sheng; Tang, Lili; Xu, Yida; Ji, Jian; Sun, Xiulan
Abstract: Fumonisin B1 (FB1) is a neurodegenerative mycotoxin synthesized by Fusarium spp., but the potential neurobehavioral toxicity effects in organisms have not been characterized clearly. Caenorhabditis elegans ( C. elegans ) has emerged as a promising model organism for neurotoxicological studies due to characteristics such as well-functioning nervous system and rich behavioral phenotypes. To investigate whether FB1 has neurobehavioral toxicity effects on C. elegans, the motor behavior, neuronal structure, neurotransmitter content, and gene expression related with neurotransmission of C. elegans were determined after exposed to 20–200 μg/mL FB1 for 24 h and 48 h, respectively. Results showed that FB1 caused behavioral defects, including body bends, head thrashes, crawling distance, mean speed, mean amplitude, mean wavelength, foraging behavior, and chemotaxis learning ability in a dose-, and time-dependent manner. In addition, when C. elegans was exposed to FB1 at a concentration of 200 μg/mL for 24 h and above 100 μg/mL for 48 h, the GABAergic and serotonergic neurons were damaged, but no effect on dopaminergic, glutamatergic, and cholinergic neurons. The relative content of GABA and serotonin decreased significantly. Furthermore, abnormal expression of mRNA levels associated with GABA and serotonin were found in nematodes treated with FB1, such as unc-30, unc-47, unc-49, exp-1, mod-5, cat-1, and tph-1 . The neurobehavioral toxicity effect of FB1 may be mediated by abnormal neurotransmission of GABA and serotonin. This study provides useful information for understanding the neurotoxicity of FB1. Graphical abstract: Image 1 Highlights: The neurobehavioral toxicity of FB1 was tested on C. elegans. FB1 induced locomotor defects of C. elegans in a time- and dose-dependent manner. Damage to GABAergic and serotonergic neurons induced by FB1 was observed. Abnormal neurotransmission might be involved in the neurotoxicity of FB1.